Evaluaciòn de bacillus thuringiensis, beauveria bassiana en tres dosis y dos frecuencias de aplicación para el control de la Mosca de la Semilla (delia platura meigen) en el Cultivo de Chocho (lupinus mutabilis sweet) en los 3 primeros meses de implantaciòn en el Chan, Latacunga, Cotopaxi 2016-2017 - Chiluisa Tiglla, Doris Vanessa (2017)
The main objective is to generate a biological control proposal for the larvae seed fly in chocho grow (Delia plantura Meigen), it was done in the neighborhood Chan in Latacunga canton, Cotopaxi, because the production of the chocho is affected in a totally way due to the severity of the attack of this pest generating considerable economic losses for producers. The resistance and proliferation of the pest in the sector should be to the traditional agriculture that is carried out by the producers so that, they do not use a technical driving of the crop of chocho (Lupinus mutabilis sweet) as a consequence it could be evidenced an inadequate organic fertilization, the M.O that is incorporated was a source of proliferation of the seed fly of chocho, because they are ovoposite in the rotting organic material. The methodologies of the study were experimental, inductive deductive field constituted by 39 experimental units in a fully alloy block design (D.B.C.A.) with 13 treatments in a factorial arrangement of 2x3x2 with 3 replicates. In which applied Bacillus thuringiensis, Bauvelia bassiana for the control of the pest in the seed of chocho in two frequencies with three different measures in each. The results of the study does not present. Statistical results were meaningful because the commercial products with they were worked not contain viable strains to consequence of external and internal factors at the moment of handling these products, in the transport and storage. In the variable height of plant at 30 and 60 days had a significant difference because the plant does not have longer life at the expense of the seed